2013
DOI: 10.1002/cite.201300066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphate Modification on the Brønsted Acidity and Methanol‐to‐Olefin Conversion Activity of Zeolite ZSM‐5

Abstract: Phosphate-modified ZSM-5 zeolites were studied by standard characterization techniques and solid-state nuclear magnetic resonance spectroscopy, and in the methanol-to-olefin (MTO) conversion. Considering the physicochemical properties of the ZSM-5 zeolites, the most important effects of the phosphate modification are a deposition of polyphosphates in the pore system and a decrease of the acid site density, but not of the acid site strength. The significant increase in the selectivity to C 2 -C 4 alkenes and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…Beside the acidic properties of zeolite catalysts, structural properties such as pore size distribution and channel length also play a key role on the stability of the alkali-treated ZSM-5 catalysts [13,53]. Since the majority of the active sites of the parent ZSM-5 catalysts are located in its micropore channels, it thus has a particular shape selectivity.…”
Section: Catalystmentioning
confidence: 98%
“…Beside the acidic properties of zeolite catalysts, structural properties such as pore size distribution and channel length also play a key role on the stability of the alkali-treated ZSM-5 catalysts [13,53]. Since the majority of the active sites of the parent ZSM-5 catalysts are located in its micropore channels, it thus has a particular shape selectivity.…”
Section: Catalystmentioning
confidence: 98%
“…S5. Aluminum atoms of P(x)-MTW exhibited two 27 Al MAS NMR peaks at 54 and −2 ppm; the former peak was attributed to the aluminum atoms with tetrahedral coordination and the latter peak to those with octahedral coordination [25,27]. The negligibly small latter peak indicated that most aluminum atoms of P(0.0)-MTW were located in its framework with a tetrahedral coordination.…”
Section: Physico-chemical Properties Of the Phosphorous-modified Mtwmentioning
confidence: 95%
“…The increase in the amount of phosphorous induced the increase in the relative intensity of the peaks at 1 and −5 ppm, while that of the peak at −11 and −18 ppm decreased considerably. The peaks at −11 and −18 ppm is attributed to the phosphorous atoms of Al O P bonds, while those at 1 and −5 ppm are from the phosphorous atoms of phosphorous oxides located in the zeolite pores [25,27]. When the amount of phosphorous was small, most phosphorous atoms were combined to aluminum atoms through oxygen atoms.…”
Section: Physico-chemical Properties Of the Phosphorous-modified Mtwmentioning
confidence: 95%
See 2 more Smart Citations